Glycosidic carbonic anhydrase IX inhibitors: a sweet approach against cancer - Winum, Jean Yves (2013)
Targeting tumour associated carbonic anhydrase (CA, EC 4.2.1.1) isoforms IX and XII is now considered as a pertinent approach for the development of new cancer therapeutics against hypoxic tumours. In the last period, with the help of X-ray crystallography, much progress has been achieved for the drug-design of selective CA IX inhibitors, by considering the three main structural elements that govern both potency and selectivity, that is, a zinc binding group (ZBG), an organic scaffold, and one or more side chains substituting the scaffold. The use of sugar moiety in the structure of sulfonamide-based CA inhibitors (CAIs), has allowed the discovery of very potent CA IX inhibitors able to impair the growth of both primary tumors and metastases. The search for specific CA IX inhibitors by using the sugar approach has become an important research field, leading to sulfonamides, sulfamates, sulfamides and coumarins with excellent in vitro activity and relevant potency in vivo, in animal models of cancer. This paper will review the latest development in this hot topic.